Role of Information, Communication and Technology (ICT) for Economic Growth of Nepal - Pokhrel, Rajendra Kumar; Pokhrel Gautam, Anju; Pokhrel, Avi (Education and Development, 2022)
Information and communication technology (ICT) refers to a broad range of technological resources and techniques used to send, store, produce, share, or exchange data or information as well as a number of technologies that make it easier to communicate, such as the internet, wireless networks, mobile phones, and other channels of communication. In this research, key informant interviews (KII) were conducted with NTA representatives, executive members, Mayor, Deputy Mayor, Ward Chairpersons of Pokhara Metropolitan City, representatives from Nepal Telecom. ICT has played a significant role in economic growth by enabling business to increase productivity, reduce costs, and improve efficiency. It can benefit a number of economic sectors, including health, education, industry, tourism, service, agriculture, culture, banking and entrepreneurship. ICT has transformed education by making it more accessible, flexible, personalized, and effective enabling learners to access educational resources from anywhere. OCE can be benefitted through ICT with respect to re-engineering of EMIS. It improves healthcare delivery by enabling remote consultations, telemedicine, and digital health records facilitates disease surveillance, monitoring, and research and improves financial inclusion through access to mobile banking, digital payments, and online financial services. Investing in human capital is critical to promoting ICT use in all sectors of the economy. Although ICT has many positive effects, it is crucial to acknowledge and deal with any negative effects in order to guarantee that technology is used responsibly and with respect.